Effectiveness Of Giving Rosella Drink To Reduce Dysminore In Adolescent Girls at Amanah 1 Middle School Medan - Wulan, Mayang; Juliani, Sri; Nabilla, Nabilla (Universitas Prima Indonesia, 2025)
The World Health Organization (WHO) estimates that in 2020, the incidence of dysmenorrhea will be 1,769,425 (90%) women suffering from dysmenorrhea, with 10-16% suffering from severe dysmenorrhea. The purpose of the study was to determine the effectiveness of providing rosella drinks in reducing dysmenorrhea in adolescent girls at SMP Amanah 1 Medan. The research method was a quasi-experimental design with a one-group pretest-posttest design. The population was all teenage girls in grades VII and VIII who experienced dysmenorrhea, totaling 32 people. The sample used a purposive sampling of 15 people. Data were collected through observation sheets and numerical rating scales. Data analysis was carried out univariately and bivariately using the sample T test. The study's results showed Frequency distribution of the dysmenorrhea pain scale at the time of the pre-test was eight people (53.3%) with a moderate pain scale, while the dysmenorrhea pain scale after giving rosella drink was 11 people (73.3%) with a mild pain scale. The results of the T-Test statistical test showed a p-value of 0.000 <0.05. The conclusion is that there is effectiveness of giving rosella drinks in reducing dysmenorrhea in female adolescents at SMP Amanah 1 Medan. It is recommended that health workers be more proactive in providing counseling on dysmenorrhea and women's reproductive health to students the education office adds a curriculum on reproductive health and schools should prepare rest areas for adolescents who experience dysmenorrhea.